The Effect of Earnings Persistence and Leverage on the Earnings Response Coefficient - Althafani Dyah Istiningtyas (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of earnings persistence and leverage on the earnings response coefficient (ERC) in basic materials sector companies of the Indonesian Stock Exchange (IDX) during the period 2021-2023. The population in this study are basic materials companies on the Indonesian Stock Exchange. This study uses a purposive sampling method and sample selected are 75 companies. Earnings persistence refers to the degree to which current earnings can predict future earnings, while leverage represents the level of a company's debt relative to its equity. The research was quantitative method, secondary data were collected from financial statements and analyzed through multiple linear regression. The results indicate that earnings persistence has a significant positive effect on the ERC, suggesting that more consistent and reliable earnings lead to stronger investor reactions. In contrast, leverage has a significant negative impact on the ERC, implying that higher debt levels may reduce investor trust in the credibility of reported earnings. These findings highlight the importance of earnings quality and capital structure in influencing investor reactions to financial performance.